Pengaruh Variasi Kandungan Serbuk Karbon Terhadap Karakteristik Mekanik Komposit Polyester Kulit Nunang - Suteja, Suteja; Hidayatullah, Syarif (Jurnal Informasi, Sains dan Teknologi, 2026)
The development and performance of high-strength, environmentally friendly, and renewable nunang fiber (Cordia dichotoma)-reinforced polyester composites continue to be refined to achieve optimal performance. This study characterizes the key properties of nunang fiber-reinforced polyester composites with carbon powder fillers. The polyester composites were fabricated using a hot-press method with a nunang fiber volume fraction of 20% (by weight) and varying carbon powder content from 0–10% (by weight). The results of the investigation show that the tensile and bending strengths of the composites increase with increasing carbon powder content up to 2.5%. However, adding carbon powder filler up to 10% to the polyester–nunang fiber composites reduces their tensile and bending strengths. A different trend is observed for the impact toughness of the composites, which increases up to a carbon powder content of 5% and decreases when the carbon powder content reaches 10%. This phenomenon is attributed to the ability to form an optimal fiber-matrix interface between the nunang fibers and the polyester–carbon powder matrix. SEM morphological observations confirmed fiber pull-out failure and matrix failure due to the high stiffness caused by the presence of the carbon powder filler.